Analisis Pengaruh Promosi dan Kualitas Produk terhadap Keputusan Pembelian Onoy Cake & Bakery di Kota Jambi - Lira Permata Utami (Science of Management and Students Research Journal (SMS), 2021)
The purpose of research is to find out the promotion, quality of products and purchasing decisions on Onoy Cake & Bakery in Jambi city. In discussing this problem the author uses qualitative descriptive methods by looking for information about the symptoms, clearly establishing the goals to be achieved, collecting data as material to make research.Onoy Cake & Bakery was founded by Suci Andhita as the owner of the business. Onoy Cake & Bakery is an UMKM that shells bread and cake. Onoy Cake & Bakery was established since 2012 until now. And Onoy Cake & Bakery have a store branch.The population in this study was consumers of Onoy Cake & Bakery in the city of Jambi. The sample was determinated by the Judgement Sampling method with a total 0f 100 customer respondents Onoy Cake & Bakery about promotion, product quality and purchasing decisions. Hypothesis tested with T test and F test.Based on the result of multiple linear analyze, the equation Y = 1,533 + 0,163.X1 + 0,661.X2+ e. the t-test value for promotion  (X1) is 2,076 and product quality (X2) is 6,618. With the F test of 0,000. The value of R square is 0,640% or 64% while the remaining 36% is influenced by other factors.The conclusion of this study is that promotion and product quality have a significant influence either simultaneous or partially on purchasing decisions.